Pengaruh Metode Kontekstual Modelling terhadap Feeding Practice pada Ibu Balita Stunting Usia 6-24 Bulan - Surani, Endang; Susilowati, Endang; Rosyidah, Hanifatur (Poltekkes Kemenkes Malang & IBI Ranting Pendidikan Kota Malang, 2023)
One of the causes of the difficulty in reducing stunting rates in toddlers is inadequate knowledge and inappropriate nutritional practices. The practice of feeding (feeding practice) is one of the factors that contribute to the incidence of stunting. Contextual modeling in this study is an educational strategy by directly involving toddler mothers in the process and applying it in everyday life. The aim of the study was to determine the effect of contextual modeling on the feeding practice of stunting toddler mothers. The type of quantitative research with the research design used is a quasi-experimental pre-post test one group design. The statistical analysis used is the Wilcoxon test and the Mann Whitney test. The research was conducted in Purwosari Village, the working area of the Sayung Demak Health Center, with a sample of 40 stunting mothers. The intervention was in the form of contextual modeling by directly practicing counseling about exclusive breastfeeding, how to make MP-ASI according to age, list of household sizes and examples of serving children's food within 1 week, while the asymptotic value sig. (2-tailed) is 0.000 and <0.05, which means the influence of contextual modeling on feeding practice. The conclusion in this study is that the provision of contextual modeling methods has an influence on feeding practice in stunted toddler mothers aged 6-24 months.